Volatility Index, Exchange Rate, Economic Growth On Stock Indexes - Junaid, Asriani; Muslim; Wilda; Darwis Said (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2024)
This study aims to analyse the effect of economic growth on the stock price index in Indonesia and Malaysia during the COVID-19 pandemic. Using regression analysis, this study measures the relationship between economic growth and the stock price index, focusing on both countries' fiscal and monetary policies. The results show that economic growth has a positive and significant effect on the stock price index in Indonesia and Malaysia, reflecting investors' optimism towards the economic outlook. Economic stimulus policies and monetary measures the government and central bank take are essential in supporting economic recovery and stock market stability. This research provides important insights for investors in making more informed investment decisions based on economic growth indicators. This study also emphasises the importance of responsive and coordinated economic policies to support economic growth and stock market stability in times of crisis.